(untitled) (Triyuga Academic Journal, 2025)
This qualitative study explores the use of Information and Communication Technology (ICT) in teaching the Nepali language at TJMC, focusing on how teachers integrate digital tools and the challenges they face. Findings reveal varied use of ICT, with mobile apps and projectors being common tools to enhance literary comprehension and student engagement. While some teachers use ICT regularly, others face limitations due to inadequate resources and training. The study highlights a significant shortage of quality Nepali digital content and insufficient teacher training as major barriers. Technical issues such as unreliable internet and power cuts also disrupt ICT use. Despite these challenges, most teachers recognize the potential of ICT to make Nepali language teaching more effective and engaging. Platforms like YouTube and Google Slides are frequently used to deliver interactive lessons. The research underscores the need for improved infrastructure, localized digital resources, and continuous professional development to maximize ICT’s benefits in Nepali language instruction and transform traditional classrooms into dynamic, learner-centered environments.